Anion control of tautomeric equilibria: Fe–H vs. N–H influenced by NH⋯F hydrogen bonding. Issue 5 (23rd November 2018) - Chambers, Geoffrey M.; Johnson, Samantha I.; Raugei, Simone; Bullock, R. Morris
Abstract : Addition of excess BF4 − to the iron hydride [Fe(P Et N Me P Et )(CO)3 H] + [B(C6 F5 )4 ] − leads to the NH tautomer, due to NH⋯F hydrogen bonding. Abstract : Counterions can play an active role in chemical reactivity, modulating reaction pathways, energetics and selectivity. We investigated the tautomeric equilibrium resulting from protonation of Fe(P Et N Me P Et )(CO)3 (P Et N Me P Et = (Et2 PCH2 )2 NMe) at Fe or N. Protonation of Fe(P Et N Me P Et )(CO)3 by [(Et2 O)2 H] + [B(C6 F5 )4 ] − occurs at the metal to give the iron hydride [Fe(P Et N Me P Et )(CO)3 H] + [B(C6 F5 )4 ] − . In contrast, treatment with HBF4 ·OEt2 gives protonation at the iron and at the pendant amine. Both the FeH and NH tautomers were characterized by single crystal X-ray diffraction. Addition of excess BF4 − to the equilibrium mixture leads to the NH tautomer being exclusively observed, due to NH⋯F hydrogen bonding. A quantum chemical analysis of the bonding properties of these systems provided a quantification of hydrogen bonding of the NH to BF4 − and to OTf − . Treatment of Fe(P Et N Me P Et )(CO)3 with excess HOTf gives a dicationic complex where both the iron and nitrogen are protonated. Isomerization of the dicationic complex was studied by NOESY NMR spectroscopy.